2017
DOI: 10.17509/jpm.v2i2.8111
|View full text |Cite
|
Sign up to set email alerts
|

Peran Efikasi Diri Dan Motivasi Belajar Dalam Meningkatkan Hasil Belajar Siswa Sekolah Menengah Kejuruan

Abstract: The purpose of this study was to analyze influence self efficacy and learning motivation to learning outcomr. This research used survey method. Data collection techniques used question model on scale of 1-5 with likert scale,. The respondents are students of Vocational High School in Kabupaten Bandung Barat . Data were analyzed using multiple linear regression. The result of the study revealed self efficacy and motivation learning both partially and simultaneously, has the positive and significant influence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
55

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 6 publications
1
12
0
55
Order By: Relevance
“…Learning outcomes are achievements through a learning process that includes cognitive, affective, and psychomotor aspects. Likewise the research conducted by Monika (Monika, 2017), provides results that are in line with Sihaloho's research. Based on the results of this study it can be concluded that the higher the level of self efficacy will contribute positively to the learning outcomes of students.…”
Section: The Relationship Between Assertiveness and Self Efficacy Witsupporting
confidence: 82%
“…Learning outcomes are achievements through a learning process that includes cognitive, affective, and psychomotor aspects. Likewise the research conducted by Monika (Monika, 2017), provides results that are in line with Sihaloho's research. Based on the results of this study it can be concluded that the higher the level of self efficacy will contribute positively to the learning outcomes of students.…”
Section: The Relationship Between Assertiveness and Self Efficacy Witsupporting
confidence: 82%
“…Motivasi berasal dari kata motif yakni kondisi dalam diri individu yang mendorong individu untuk melakukan aktivitas tertentu baik disadari maupun tidak untuk mencapai tujuan tertentu (Winarni, Anjariah, & Romas, 2016). Motivasi belajar dapat diartikan sebagai daya pendorong untuk melakukan aktivitas belajar tertentu yang berasal dari dalam diri dan juga dari luar individu sehingga menumbuhkan semangat dalam belajar (Monika & Adman, 2017). Motivasi belajar merupakan syarat mutlak untuk belajar dan memegang peranan penting dalam memberikan gairah atau semangat dalam belajar.…”
Section: Motivasi Belajarunclassified
“…Learning facilities can be said to be complete if students have the facilities and infrastructure needed in the learning process, including: comfortable classrooms, writing desks, chairs, books and stationery. Monika & Adman (2017) explained that facilities in learning will make students more enthusiastic, motivated, not easily bored, helping students and teachers in carrying out the learning process. So that it requires completeness directly or indirectly with students in supporting the smoothness and success of the learning process such as learning media, learning tools, school supplies, and others.…”
Section: Discussionmentioning
confidence: 99%